Effects of acute, intermittent exercise in hypoxic environments on the release of cardiac troponin - Li, F.; Hu, Y.; Nie, J.; Fu, F. H. (Scandinavian Journal of Medicine & Science in Sports, 2016)
The purpose of this study was to examine the effects of acute, intermittent exercise performed in hypoxic environments on the release of cardiac troponin (cTn). Ten well-trained, male marathon runners (22.1 ± 2.6 years, 64.0 ± 4.9 kg and 177.3 ± 3.9 cm) completed three intermittent exercise protocols under normoxic (trial N) and hypoxic (trial AH and RH) conditions. In trial N, the fraction of inspiration oxygen (FIO2) was 21.0% and exercise intensity was 90% and 50% normoxic velocity of VO2max (vVO2max). In trial AH, FIO2 was 14.4% (simulated altitude of 3000 m) and exercise intensity was 90% and 50% normoxic vVO2max. In trial RH, FIO2 was 14.4% and exercise intensity was 90% and 50% hypoxic vVO2max. High-sensitivity cardiac troponin T (hs-cTnT) and cardiac troponin I (cTnI) were measured pre- and 0, 2, 4, and 24 h post-exercise. Hs-cTnT was elevated in all three trials, peaking at 2 to 4 h and returning to the baseline 24 h post-exercise. CTnI increased in trial AH, peaking at 2 to 4 h and returning below the detection limit 24 h post-exercise. It is concluded that the stimulus of hypoxia did not in and of itself induce more cTn to be released, but exercise intensity could affect this response in hypoxic environments.